THE IMPLEMENTATION OF TELL A STORY METHOD BASED ON STORY OF PROPHET YUSUF A.S. IN EMBEDDING CHARACTER WITH BEING HONEST FOR 5-6 YEARS OLD CHILDREN AT RA MADINATUL QUR'AN - Masitoh, Siti; Sudrajat, Sanin; Rini, Ratu Yustika; Hidayat, Amat; Mutoharoh, Mutoharoh (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
This study aims to determine how the storytelling method of the Prophet Yusuf (peace be upon him) can be used to instill the value of honesty in 5-6 years-old children at RA Madinatul Qur'an. Honesty is a very important value to be developed from an early age, yet dishonest behavior still occurs among children. The method used in this study was a descriptive qualitative approach using observation, interviews, and document collection techniques. The subjects in this study consisted of a teacher and five children. The findings of the study indicate that the storytelling method was implemented through sound planning and implementation, utilizing visual media and expressive delivery. The children demonstrated understanding and behavioral changes that reflect honesty, such as the ability to admit mistakes and summarize the story's content. The story of the Prophet Yusuf (peace be upon him) has proven effective as a means of instilling moral values that touch children's emotional aspects. Furthermore, the storytelling method is also recognized as a fun and meaningful approach to character education for early childhood.